Fetomaternal Outcome of Eclampsia - Begum, Fatema; Sharmin, Bedoura; Zakia, Umme Hafsa; Dewan, Farhana; Asaduzzaman, SM (KYAMC Journal, 2018)
Background: Eclampsia is a leading cause of maternal mortality and morbidity and adverse neonatal outcome. Healthcare system must be enhance to improve fetomaternal outcome. Objective: To find out the proportion and fetomaternal outcome of eclampsia. Materials and Methods: A cross sectional descriptive study was conducted to assess the fetomaternal outcome of eclampsia. The study was carried out at the Eclampsia unit, Dhaka Medical College Hospital, Dhaka over aperiod of six months from 1st July 2008 to 31st December 2008. A total of 48 patients with diagnosis of antepartum and intrapartum eclampsia were consecutively taken in the study. The test statistics used to analyse the data were descriptive statistics. Results: About 7% of patients developed acute renal failure,16.7% CVA,14.6% HELLP syndrome and 39.6% pulmonary oedema. The mean hospital stay was 9.5 ± 3.3 days. Majority (93.8%) of the patients recovered while 6.3% died. Twenty-seven (54.2%) neonates had to be referred to neonatal intensive care unit for better management. Of them 24 recovered following resuscitation. The mean weight of baby was 2.2±0.3 kg. Conclusion: Eclampsia is still a major cause of maternal mortality and morbidity in Bangladesh. Monitoring of high-risk patients may reduce the complication rate. KYAMC Journal Vol. 9, No.-3, October 2018, Page 120-124